2022
DOI: 10.3389/fnagi.2022.1095081
|View full text |Cite
|
Sign up to set email alerts
|

An update on the use of gamma (multi)sensory stimulation for Alzheimer’s disease treatment

Abstract: Alzheimer’s disease (AD) is characterized by reduced fast brain oscillations in the gamma band (γ, > 30 Hz). Several animal studies show that inducing gamma oscillations through (multi)sensory stimulation at 40 Hz has the potential to impact AD-related cognitive decline and neuropathological processes, including amyloid plaques deposition, neurofibrillary tangles formation, and neuronal and synaptic loss. Therefore Gamma Entrainment Using Sensory stimulation (GENUS) is among the most promising approache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 76 publications
(101 reference statements)
0
12
0
Order By: Relevance
“…Numerous preclinical studies have shown that such gamma stimulation attenuates amyloid and tau pathology and promotes neuroprotection in mouse models of AD and that this coincides with improvements in cognitive function [7][8][9][10][11][12][13][14]. Based on these findings, multiple clinical trials have focused on assessing the therapeutic potential of gamma stimulation and encouragingly show gamma stimulation can also ameliorate aspects of neurodegeneration and dementia in patients with AD [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous preclinical studies have shown that such gamma stimulation attenuates amyloid and tau pathology and promotes neuroprotection in mouse models of AD and that this coincides with improvements in cognitive function [7][8][9][10][11][12][13][14]. Based on these findings, multiple clinical trials have focused on assessing the therapeutic potential of gamma stimulation and encouragingly show gamma stimulation can also ameliorate aspects of neurodegeneration and dementia in patients with AD [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The attempts to restore/influence gamma power in AD are still at an investigational stage, as no changes in AD biomarkers in humans after such treatment have been reported to date (Manippa et al, 2022). However, gamma‐patterned AD treatment has a clear clinical potential because a steady state gamma induced in sensory cortex can propagate into deeper brain areas in rodents (Adaikkan et al, 2019; Li et al, 2021; Martorell et al, 2019; Soula et al, 2023) and humans (Jones et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Agents that directly pharmacologically target major neuropathological hallmarks of the disease including beta‐amyloid (Aß) plaques, tau‐containing neurofibrillary tangles and neuroinflammation are the main focus of attention (Cummings et al, 2022; van Dyck et al, 2023). In addition, the therapeutic potential of non‐pharmacological approaches, including those targeting brain network dysfunction, is gaining considerable traction (Chen et al, 2022; Manippa et al, 2022). Abnormal brain network activity in patients with AD includes a marked reduction in gamma band electroencephalogram oscillations (γ, 30–100 Hz) (Casula et al, 2022), a feature that also has been observed in many animal models (Bazzigaluppi et al, 2018; Driver et al, 2007; Iaccarino et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although the exact mechanism of action of tACS is still under debate, the explicit aim of gamma-tACS is to restore disrupted endogenous gamma oscillations in AD patients. tACS is presumed to entrain or stimulation, can entrain gamma oscillations in AD patients for therapeutic purposes (Manippa et al, 2022). Indeed, the seminal study of Clements-Cortes and colleagues demonstrated that six 30-minute sessions of 40 Hz vibrotactile stimulation improve cognitive functioning in AD (Clements-Cortes et al, 2016).…”
Section: Proposed Mechanisms Of Action Of Gamma-tacsmentioning
confidence: 99%